PENGELOLAAN HUTAN BERBASIS BUDAYA LOKAL DI DUSUN PEJAM KABUPATEN BANGKA: Tim Jarlit Kebudayaan Bappeda Prov.Kep.Bangka Belitung - Jamilah Cholillah (Society, 2017)
Forests have an important and substantial significance for the survival of the Lom. Without the forest, Orang Lom can not guarantee his life well and prosperous. Prosperous here has two important meanings, namely the outer welfare that is; They live and work together with the forest, part of the forest, by cultivating, gardening, farming, and taking the raw materials to support life such as wood, rattan, honey, medicine and water supply as well as fruits, Fruits. In the context of the soul, the forest is a guarantee of spiritual welfare for the realm of belief that we call the natural theology of the Lom. The forest is the home of life, and also a place of freedom and sacred worship.